2003
DOI: 10.1021/jo0267551
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Transesterification/Acylation Reactions Mediated by N-Heterocyclic Carbene Catalysts

Abstract: Imidazol-2-ylidenes, a family of N-heterocyclic carbenes (NHC), are efficient catalysts in the transesterification involving numerous esters and alcohols. Low catalyst loadings of aryl- or alkyl-substituted NHC catalysts mediate the acylation of alcohols with enol acetates in short reaction times at room temperature. Commercially available and more difficult to cleave methyl esters react with primary alcohols in the presence of alkyl-substituted NHC to efficiently form the corresponding esters. While primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(98 citation statements)
references
References 56 publications
2
93
1
1
Order By: Relevance
“…Under identical experimental conditions, the following series for the efficiencies emerged for the carbene catalysts that were examined: 2d (0) < 1a (1,0) < 1b 1,5) < 7 (1,8) < 8a (3,7) < 8b (6,2) < 9 (6,0) < 10 (6,7) < 2a (9,3) < 3b (10,0) < 3a (10,3) < 4 (12,0) < 5 (12,6) < 6 (12,9) < 3c = 2b (13,3) < 2c = 11 (13,4).…”
Section: Catalytic Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under identical experimental conditions, the following series for the efficiencies emerged for the carbene catalysts that were examined: 2d (0) < 1a (1,0) < 1b 1,5) < 7 (1,8) < 8a (3,7) < 8b (6,2) < 9 (6,0) < 10 (6,7) < 2a (9,3) < 3b (10,0) < 3a (10,3) < 4 (12,0) < 5 (12,6) < 6 (12,9) < 3c = 2b (13,3) < 2c = 11 (13,4).…”
Section: Catalytic Resultsmentioning
confidence: 99%
“…Since stable carbenes are highly basic compounds (pKa 21-28) they have also been suggested as catalysts for the transesterification reaction. [2][3][4][5][6][7][8] The latter reaction is typically carried out at room temperature in the presence of 0.5-5.0 mol% of carbenes and molecular sieves. The efficiencies of the catalysts can be estimated on the basis of the values of TON and TOF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…397,398 The carbene was combined with stoichiometric amounts of the required reagents in the presence of molecular sieves. [399][400][401] In the first case, catalysis with imidazol-2-ylidenes in the presence of primary alcohols, resulted values for TON and TOF of 17-19 and 1 h ) but proceeds irreversibly due to the release of acetaldehyde.…”
Section: Catalysis By Carbenesmentioning
confidence: 99%
“…In 1994, Bakhiar and Smith found that acyl transfers could be promoted by stoichiometric amounts of stable carbenes [113]. In 2002, Nolan's [51] and Hedrick's [52] research groups reported that N-heterocyclic carbenes (NHC) such as 17 and 18 (imidazol-2-ylidenes) are efficient catalysts in the transesterification of esters and alcohols [53,114], as exemplified by Scheme 11. N-Heterocyclic carbenes act as catalysts for living ring-opening polymerizations of lactones, generating polyesters [115,116] (see e.g., Scheme 4).…”
Section: N-heterocyclic Carbene-catalyzed Transesterificationsmentioning
confidence: 99%